Women's hidden harvest: Indigenous vegetables and amaXhosa cultural survival in Hobeni Village, South Africa - Tavenner, Katie (Bioversity International, 2018)
This book is about the people of Hobeni Village and the protected area that neighbors them, the Dwesa-Cwebe Nature Reserve.